PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENGGELAPAN PAJAK (Tax Evasion) - PUTRI SARI NILAM CAYO (Fakultas Hukum Universitas IBA Palembang, 2021)
A criminal act because it is an engineering subject (perpetrator) and object (transaction) of taxes to obtain tax savings unlawfully (unlawfully), and tax evasion can be said to be an inherent virus in every tax system that applies in almost every jurisdiction. Taxes in Indonesia are no longer foreign. Almost every day people are presented with news about corruption, of course tax evasion is still included in corruption. The problem in this paper is how the criminal responsibility for the perpetrators of tax evasion (Tax Evasion) As for the conclusions of this paper, the forms of criminal liability for perpetrators of tax evasion are regulated in Article 38, Article 39 and Article 41 a and b of Law Number 16 Year 2009 concerning General Provisions and Tax Procedures.